Adoption of Cattle Cross Breeding: A Study of Farmers’ Attitude in Bidar District of Karnataka - Rathod, Prakashkumar; Hiremath, Siddaling Swamy; Prakash , A.G. Bhanu (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
An ex-post-facto and exploratory study was conducted to explore the attitude of 200 dairy farmers towards cross breeding and factors affecting its adoption using pretested interview method in Bidar District of Karnataka. The study revealed that majority of the dairy farmers (74.0 %) belong to medium level of favorability followed by high and low level of favourable attitude towards cross breeding. About 85 per cent respondents perceived that adoption of cross breeding would give them better recognition in society and about 74 per cent farmers felt that cross breeding was essential to improve milk production. The results show that there is a need to give greater emphasis to educate the farmers regarding cross breeding for effective adoption and popularization of the technology.
Keywords: Adoption; Attitude; Cross breeding; Karnataka